RNA-Seq Analysis of the Growth Hormone Transgenic Female Triploid Atlantic Salmon (Salmo salar) Hepatic Transcriptome Reveals Broad Temperature-Mediated Effects on Metabolism and Other Biological Processes - Ignatz, Eric H.; Hori, Tiago S.; Kumar, Surendra; Benfey, Tillmann J.; Braden, Laura M.; Runighan, C. Dawn; Westcott, Jillian D.; Rise, Matthew L. (Frontiers in Genetics, 2022)
This study examined the impact of rearing temperature (10.5, 13.5 or 16.5 °C) on the hepatic transcriptome of AquAdvantage Salmon (growth hormone transgenic female triploid Atlantic salmon) at an average weight of 800 g. Six stranded PE libraries were Illumina-sequenced from each temperature group, resulting in an average of over 100M raw reads per individual fish. RNA-sequencing (RNA-seq) results showed the greatest difference in the number of differentially expressed transcripts (1750 DETs), as revealed by both DESeq2 and edgeR (q < 0.05; fold-change > |1.5|), was between the 10.5 and 16.5 °C temperature groups. In contrast, 172 and 52 DETs were found in the 10.5 vs. 13.5 °C and the 13.5 vs. 16.5 °C comparisons, respectively. Considering the DETs between the 10.5 and 16.5 °C groups, 282 enriched gene ontology (GO) terms were identified (q < 0.05), including 'response to stress', 'immune system process', 'lipid metabolic process', 'oxidation-reduction process' and 'cholesterol metabolic process', suggesting elevated temperature elicited broad effects on multiple biological systems. Pathway analysis using ClueGO showed additional impacts on amino acid and lipid metabolism. There was a significant positive correlation between RNA-seq and real-time quantitative polymerase chain reaction (RT-qPCR) results for 8 of 9 metabolic-related transcripts tested. RT-qPCR results also correlated to changes in fillet tissue composition previously reported in these salmon (e.g., methionine and lysine concentrations positively correlated with hsp90ab1 transcript expression), suggesting that rearing temperature played a significant role in mediating metabolic/biosynthetic pathways of AquAdvantage Salmon. Many transcripts related to lipid/fatty acid metabolism (e.g., elovl2, fabpi, hacd2, mgll, s27a2, thrsp) were downregulated at 16.5 °C compared to both other temperature groups. Additionally, enrichment of stress-, apoptosis- and catabolism-relevant GO terms at 16.5 °C suggests that this temperature may not be ideal for commercial production when using freshwater recirculating aquaculture systems (RAS). This study relates phenotypic responses to transcript-specific findings and therefore aids in the determination of an optimal rearing temperature for AquAdvantage Salmon. With approval to grow and sell AquAdvantage Salmon in the United States and Canada, the novel insights provided by this research can help industry expansion by promoting optimal physiological performance and health.